Nafion-impregnated electrospun polyvinylidene fluoride composite membranes for direct methanol fuel cells - Choi, S. W.; Fu, Y. -Z.; Ahn, Y. R.; Jo, S. M.; Manthiram, A. (ELSEVIER SCIENCE BV, 2008)
Composite membranes consisting of polyvinylidene fluoride (PVdF) and Nafion have been prepared by impregnating various amounts of Nafion (0.3-0.5 g) into the pores of electrospun PVdF (5 cm x 5 cm) and characterized by scanning electron microscopy, differential scanning calorimetry, X-ray diffraction, and proton conductivity measurements. The characterization data suggest that the unique three-dimensional network structure of the electrospun PVdF membrane with fully interconnected fibers is maintained in the composite membranes, offering adequate mechanical properties. Although the composite membranes exhibit lower proton conductivity than Nafion 115, the composite membrane with 0.4 g Nafion exhibits better performance than Nafion 115 in direct methanol fuel cell (DMFC) due to smaller thickness and suppressed methanol crossover from the anode to the cathode through the membrane. With the composite membranes, the cell performance increases on going from 0.3 to 0.4 g Nafion and then decreases on going to 0.5 g Nafion due to the changes in proton conductivity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: POLYMER ELECTROLYTE MEMBRANES; NANOFIBERS; CROSSOVER